Complementary mRNA expression of enzymes producing nitric oxide and prostaglandin in ductus arteriosus with respect to their role in maintaining patency. (4th January 2023) - Yamana, Rei; Kadota, Shogo; Ishii, Kazuaki; Suzuki, Takehito; Miyazaki, Yoko; Tanaka, Kazuaki; Usami, Makoto; Takizawa, Tatsuya
Abstract: mRNA expression of molecules related to the activity of nitric oxide or prostaglandin E2, the critical regulators maintaining the ductus arteriosus patency, was examined in rat ductus arteriosus at preterm (days 18.5 and 19.5 of pregnancy) and near term (days 20.5 and 21.5). The endothelial nitric oxide synthase mRNA level increased transiently at preterm and then decreased at near term. The cyclooxygenase 2 mRNA increased gradually from near‐term to the term complementary to the reduced endothelial nitric oxide synthase mRNA. These results suggest that the role shift between nitric oxide and prostaglandin E2 in maintaining ductus arteriosus patency at preterm and near term may be due to complementary expression changes of endothelial nitric oxide synthase and cyclooxygenase 2 at the transcriptional level.